Plotting current practices and challenges among Indonesian occupational therapists working with individuals with autism spectrum disorders. Issue 2 (3rd July 2021) - Saloko, Erayanti; Harumi, Linda; Sumaryanto, Eko; Kobayashi, Ryuji; Ito, Yuko
ABSTRACT: Indonesian occupational therapists, despite being few in numbers, face a high demand for quality care due to the high prevalence of Autism Spectrum Disorders (ASD). Hence, there is a need to investigate how Indonesian occupational therapists render services for individuals with ASD. The objectives of this study were to describe Indonesian occupational therapy practice and identify the challenges in rendering services for individuals with ASD. This cross-sectional study employed an online survey with structured and open-ended questions to collect data from Indonesian occupational therapists who work with persons with ASD. Descriptive statistics and thematic analysis were used to analyse data. Survey was completed with an 88% response rate. Sensory Integration and Short Sensory Profile are the most common frame of reference and standardised assessment, respectively. Challenges identified were: translating theory into practice, being creative and skilful, improving competence for effective collaboration, supporting parental involvement, and overcoming stigma. This study clarified the nature of current Indonesian occupational therapy practice for individuals with ASD and the challenges faced by Indonesian OTs in rendering services for persons with ASD.